'Keeping the kids at home' can limit the persistence of contagious pathogens in social animals. Issue 11 (14th September 2021) - Marescot, Lucile; Franz, Mathias; Benhaiem, Sarah; Hofer, Heribert; Scherer, Cédric; East, Marion L.; Kramer‐Schadt, Stephanie
Abstract: Social networks are considered to be 'highly modular' when individuals within one module are more connected to each other than they are to individuals in other modules. It is currently unclear how highly modular social networks influence the persistence of contagious pathogens that generate lifelong immunity in their hosts when between‐group interactions are age dependent. This trait occurs in social species with communal nurseries, where juveniles are reared together for a substantial period in burrows or similar forms of containment and are thus in isolation from contact with individuals in other social groups. Our main objective was to determine whether, and to what extent, such age‐dependent patterns of between‐group interactions consistently increased the fade‐out probability of contagious pathogens that generate lifelong immunity in their hosts. We hypothesised that in populations of species where juveniles are raised in communal nurseries, a high proportion of recovered adults in a group would form a 'protective barrier' around susceptible juveniles against pathogen transmission, thereby increasing the probability of epidemic fade‐out in the population. To test this idea, we implemented a spatially implicit individual‐based susceptible–infected–recovered (SIR) model for a large range of generic host and pathogen traits. Our results indicated that (a) the probability of epidemic fade‐out was consistently higher in populations with communal nurseries, especially for highly contagious pathogens (high basic reproduction number, R 0 ) and (b) communal nurseries can counteract the cost of group living in terms of infection risk to a greater extent than variation in other traits. We discuss our findings in relation to herd immunity and outline the importance of considering the network structure of a given host population before implementing management measures such as vaccinations, since interventions focused on individuals with high between‐group contact should be particularly effective for controlling pathogen spread in hosts with communal nurseries. Abstract : Using a spatially implicit individual‐based susceptible‐infected‐recovered (SIR) model, the authors show that in host populations where juveniles are isolated from contact with individuals in other social groups, the transmission and persistence of contagious pathogens is reduced. The likely mechanism is the formation, in social groups, of protective barriers composed of recovered adults around the new generations of susceptible juveniles. Zusammenfassung: Soziale Netzwerke werden als "hochmodular" bezeichnet, wenn Individuen innerhalb eines Moduls, wie z. B. einer sozialen Gruppe, stärker miteinander verbunden sind als mit Individuen anderer Module. Es ist derzeit unklar, wie hochmodulare soziale Netzwerke die Persistenz von ansteckenden Krankheitserregern beeinflussen, die lebenslange Immunität in ihren Wirten erzeugen, wenn die Interaktionen zwischen den Gruppen altersabhängig sind. Dieses Merkmal tritt bei sozialen Arten mit gemeinschaftlichen Kinderstuben auf, bei denen Jungtiere über einen längeren Zeitraum gemeinsam in Höhlen oder ähnlichen Formen der Eingrenzung aufgezogen werden und somit vom Kontakt mit Individuen anderer sozialer Gruppen isoliert sind. Unser Hauptziel war es, festzustellen, ob und in welchem Ausmaß gemeinschaftliche Kinderstuben die Aussterbewahrscheinlichkeit von ansteckenden Krankheitserregern erhöhen, die lebenslange Immunität in ihren Wirten erzeugen. Wir stellten die Hypothese auf, dass in Populationen von Arten, in denen Jungtiere in gemeinschaftlichen Kinderstuben aufgezogen werden, ein hoher Anteil an genesenen Erwachsenen in einer Gruppe eine "schützende Barriere" um anfällige Jungtiere gegen die Übertragung von Krankheitserregern bildet und damit die Aussterbewahrscheinlichkeit von Epidemien in der Population erhöht. Um diese Idee zu testen, haben wir ein räumlich implizites individuenbasiertes susceptible‐infected‐recovered (SIR)‐Modell für generische Wirts‐ und Pathogenmerkmalen implementiert. Unsere Ergebnisse deuten darauf hin, dass (i) die Aussterbewahrscheinlichkeit von Krankheitserregern in Populationen mit gemeinschaftlichen Kinderstuben durchweg höher war, insbesondere für hochansteckende Erreger (hohe Basisreproduktionszahl, R0) und (ii) dass gemeinschaftliche Kinderstuben den Kosten des Gruppenlebens in Bezug auf das Infektionsrisiko in größerem Maße entgegenwirken können als andere Parameter. Wir diskutieren unsere Ergebnisse in Bezug auf die Herdenimmunität und zeigen auf, wie wichtig es ist, die Netzwerkstruktur einer gegebenen Wirtspopulation zu berücksichtigen, bevor Managementmaßnahmen wie Impfungen durchgeführt werden, da Interventionen, die sich auf Individuen mit hohem Kontakt zwischen den Gruppen konzentrieren, besonders effektiv für die Kontrolle der Erregerausbreitung in Wirten mit gemeinschaftlichen Kinderstuben sein können.